Pengaruh Latihan Renang terhadap Kebugaran Jasmani Anak SD di Desa Tampakang - Rifa'i, Ahmad; Baihaqi, Mohammad (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
Fitness is a crucial component of the human body, especially for children. During this period, children experience rapid growth and development, both physically, mentally, and socially. Physical fitness is influenced by physical activity and sports training that a person does, so the better the level of physical fitness. Physical activities carried out routinely will have a positive impact on physical fitness. One effective way to improve physical fitness is swimming. Swimming is a situation where the swimmer must float on the water. This study aims to determine the effect of swimming training on children's physical fitness in Tampang Village. This study uses a quantitative approach with a data collection technique in the form of a questionnaire. The sample in this study was 15 children. The research instrument has been tested for validity and reliability and meets the requirements of normal distribution. This study produces a conclusion, namely that there is a significant influence between swimming training and children's physical fitness. This is evidenced by a simple linear regression analysis showing that swimming training has a significant effect on children's physical fitness. The significance value of 0.000 <0.05 and t count of 5.356> t table 2.160, and the coefficient of determination (R Square) value of 0.688 indicates that swimming training has an effect of 68.8% on children's physical fitness.